Formation of Cisplatin Adducts with the Epigenetically Relevant Nucleobase 5‐Methylcytosine. Issue 1 (19th November 2020) - Menke, Annika; Dubini, Romeo C. A.; Mayer, Peter; Rovó, Petra; Daumann, Lena J.
Abstract : With about 4 % abundance in the genome 5‐methylcytosine (5mC ) is one of the most important epigenetic modifications. Change in DNA hypermethylation levels has even been linked to resistances to cisplatin treatment of cancer cells. This work aimed at the synthesis and full characterization of 5mC ‐cisplatin adducts as well as for the examination of possible side‐reactions and transformations. We report the first X‐ray crystal structure of a cis ‐[PtCl(5mC )(NH3 )2 ]Cl complex and the formation of [PtCl(5mC )(NH3 )2 ] + and [PtCl(5mC )2 (NH3 )] + with HR‐ESI mass spectrometry. Further, we explore complex formation and dynamics using 1 H, 195 Pt, and DOSY NMR spectroscopy. UV/Vis absorption and EPR spectroscopy also confirmed the formation of trace amounts of paramagnetic Pt‐blue species. In the process, a hemiprotonated 5mC dimer, 5mC ‐5mC H +, reminiscent of the "i‐motif" in DNA tetramers, was structurally characterized. Abstract : The complexity of cisplatin‐nucleobase chemistry: Identification of a cisplatin‐5‐methylcytosine complex cis ‐[PtCl(5mC )(NH3 )2 ]Cl out of a pool of complex mixtures. Using 1 H, 195 Pt, DOSY NMR spectroscopy, HR‐MS spectrometry as well as EPR and UV/Vis spectroscopy, multiple products obtained after the reaction of cisplatin with 5mC were characterized.